Eksekusi Jaminan Fidusia: Mengamankan Aset Kreditur atau Melindungi Harta Debitur - Junjung Sahala Tua Manik; Retno Sunu Astuti; Ida Hayu Dwimawanti (Jurnal Administrasi Bisnis, 2020)
The published of the Fiduciary Law (UUJF) No 42 of 1999 to provide legal security for credit financing vehicles. One of the legal security is who the executor when credit was bad debt. In fiduciary law, the authority to execution is on the creditor. The goal of the execution must be peaceful, without conflict. Implementation Grindle's theory on this research found that many executions caused a commotion and conflicts, disturb the debtor and others. This condition shows that fiduciary law has not succeeded in protecting the interested parties, debtors, and creditors. A good policy gives benefits to the target group. Conflicts show a failure of the implementation of fiduciary law. This research found content and context policy to obstruct implementation. Execution by creditors always prejudice debtors, therefore execution by creditors is banned, parallel with the judgment of the Constitutional Court.